Sejarah Sistem Pendidikan Indonesia: Masa Penjajahan, Masa Kemerdekaan, Masa Reformasi-Sekarang - Hilda Lutfiya; Himatul Uliya; Ida MartafiaPutri; Mambaul Ngadhimah (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
This journal examines the development of the education system in Indonesia from the Dutch colonial period to the reform era, focusing on the educational policies implemented and their impact on society. This research uses qualitative methods with a literature study approach, collecting primary data from key literature and secondary data from related articles and journals. The results of the analysis show that during the colonial period, education was discriminatory and only benefited a handful of elites, whereas during the New Order era, there was success in literacy eradication programs and the implementation of a six-year compulsory education, which later expanded to nine years. The journal also highlights the importance of curriculum changes to improve the quality of education and to adapt to the demands of the times.